2010
DOI: 10.1097/mpg.0b013e3181d33b7d
|View full text |Cite
|
Sign up to set email alerts
|

Constipation‐associated and Nonretentive Fecal Incontinence in Children and Adolescents: An Epidemiological Survey in Sri Lanka

Abstract: FI is not uncommon among children and adolescents of 10 to 16 years of age in Sri Lanka with a male predilection. Some predisposing factors, such as exposure to stressful life events and being bullied at school, which are similar to those described in the literature for FI, could be clearly recognized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 21 publications
4
61
1
2
Order By: Relevance
“…Recently, a study in a primary care clinic of 482 US children aged 4 to 7 years, reported a prevalence of 4.4%, with 95% having underlying constipation [17]. In another epidemiologic study in Sri Lanka, fecal incontinence was present in 2% of the general population, with 82% having it associated with constipation [13]. In this study, the highest prevalence was 5.4% in children 10 years of age.…”
Section: Coexistence Of Constipation and Incontinence In Childrenmentioning
confidence: 54%
See 2 more Smart Citations
“…Recently, a study in a primary care clinic of 482 US children aged 4 to 7 years, reported a prevalence of 4.4%, with 95% having underlying constipation [17]. In another epidemiologic study in Sri Lanka, fecal incontinence was present in 2% of the general population, with 82% having it associated with constipation [13]. In this study, the highest prevalence was 5.4% in children 10 years of age.…”
Section: Coexistence Of Constipation and Incontinence In Childrenmentioning
confidence: 54%
“…Functional fecal incontinence in children is a common problem, reported in 1–4% of school-aged children [4, 9, 12, 13]. The reported prevalence among children 4 years of age was 2.8%, in those 7–8 years, it was 2.3% for boys and 1.3% for girls [14], and among 10–12-year-olds, 1.3% for boys and 0.3% for girls [15].…”
Section: Coexistence Of Constipation and Incontinence In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they are also likely to get emotionally abused at schools by peers and even by teachers because of the incessant smell of feces around them. In a previous study FI was clearly shown to be associated with emotional stress (16). The stress of abuse and symptoms may push the child more toward an unbreakable vicious cycle of stress and FI.…”
Section: Discussionmentioning
confidence: 97%
“…The rate in children aged 10 and 11 years was found to be 1.6%. This condition was observed three to six times more often in boys than in girls (3:1 to 6:1) (12)(13)(14).…”
Section: Epidemiologymentioning
confidence: 97%